Design, synthesis and biological evaluation of new 3, 4-dihydroquinoxalin-2(1H)-one derivatives as soluble guanylyl cyclase (sGC) activators. Issue 11 (November 2022) - Kintos, Dionysios-Panagiotis; Salagiannis, Konstantinos; Vazoura, Vasiliki; Wittrien, Theresa; Papakyriakou, Athanasios; Nikolaropoulos, Sotiris S.; Behrends, Soenke; Topouzis, Stavros; Fousteris, Manolis A.
Abstract: Herein, we present the structure-based design, synthesis and biological evaluation of novel mono- and di-carboxylic 3, 4-dihydroquinoxalin-2(1 H )-one derivatives as potential heme-independent activators of soluble guanylate cyclase (sGC). Docking calculations of several known sGC agonists by utilizing both a homology model of human sGC β1 Η-ΝΟΧ domain and a recent cryo-EM structure of the same domain guided the structural optimization of various designed compounds. Among these, mono- and di-carboxylic 3, 4-dihydroquinoxalin-2(1 H )-one derivatives arose as promising candidate sGC activators. A series of such compounds was synthesized and assessed for their effect on sGC activity. None of them was able to trigger any detectable activation of native sGC in prostate cancer (LnCaP) or rat aortic smooth muscle (A7r5) cells, even after loss of heme by treatment with the heme oxidant ODQ. Furthermore, selected derivatives did not exhibit any antagonistic effect against the known heme-independent sGC activator BAY 60-2770 nor any additive or synergistic effect with the heme-dependent NO donor sodium nitroprusside (SNP) on heme-associated sGC in A7r5 cells. However, when tested in vitro using purified recombinant sGC enzyme, the dicarboxylic 3, 4-dihydroquinoxalin-2(1 H )-one derivative 30d was able to increase the enzymatic activity of both the wild-type α1/β1 sGC dimer (by 4.4-fold, EC50 = 0.77 μΜ) as well as the heme-free α1/β1 His105Ala mutant sGC (by 4.8-fold, EC50 = 1.8 μΜ). Notably, the activity of compound 30d towards the mutant α1/β1 Η105A enzyme was comparable with that previously reported by us for the bona fide activator BAY 60-2770, using the functionally equivalent wild-type sGC preparation treated with ODQ. These results indicate that compound 30d can indeed act as a promising sGC activator and may serve as a basic structure in the design of novel, optimized analogues with enhanced sGC agonistic activity and improved efficiency in cell-based and in vivo systems. Graphical abstract: Image 1 Highlights: Novel 3, 4-dihydroquinoxalin-2(1H)-ones were designed and synthesized. Compounds were evaluated for activation of sGC in enzyme- and cell-based assays. Analogue 30d increased the activity of both the wild-type and mutant His105Ala sGC. 30d induces maximum enzyme activity comparable with that of activator BAY 60-2770. Abstract : Nitric oxide; Soluble guanylyl cyclase; sGC activators; 3, 4-Dihydroquinoxalin-2(1H)-one.